Development of Augmented Reality-Based Learning Media for Ship Navigation Instruments as an Educational Innovation at the Merchant Marine Polytechnic of Makassar - Lestari, Endang; M Masrupah; Ridwan, Wardimansyah; Lammi, Muhammad Hidayat (CV. Media Digital Publikasi Indonesia, 2026)
Navigation instruments such as GPS, Radar, and ECDIS require substantial investment and continuous maintenance, which limits their availability for routine hands-on practice in maritime training. As a result, cadets may have fewer opportunities to experience learning conditions that closely resemble real operational environments. This study, conducted at the Merchant Marine Polytechnic of Makassar, aimed to develop an Augmented Reality (AR)-based learning application that visualizes ten essential ship navigation instruments: GPS, Radar, ECDIS, AIS, Gyrocompass, Echo Sounder, Autopilot, Speed Log, VHF Radio, and NAVTEX. The development followed the Multimedia Development Life Cycle (MDLC) model, including 3D object creation, marker integration, and Android application development using Unity and Vuforia. The feasibility of the application was evaluated through expert validation and field testing involving 115 cadets. Expert evaluation showed that functionality, usability, and reliability met the “Good” to “Very Good” categories, with an overall score of 84%. Cadet trials also indicated consistently positive responses, particularly in conceptual understanding, learning motivation, and ease of use, with one minor issue related to longer scanning time for a marker. Overall, the findings suggest that AR Marine NavTool is feasible for use in maritime vocational education and can serve as a preparatory learning layer that supports more structured progression to hands-on practice through accessible and interactive visualization of navigation instruments.